An Analysis of English Code Switching and Code Mixing Used in Narrative story during Speaking Class : An Analysis of English Code Switching and Code Mixing Used in Narrative story during Speaking Class - Cicik Ristiamadani; Ahmad Tauchid; Cicik Ristiamadani; Ahmad Tauchid (INTENS (International Journal of English Education and Linguistics), 2025)
The primary objective of this study was to identify the instances of Code Switching and Code Mixing employed during narrative storytelling in a classroom speaking class. Additionally, it aimed to highlight the advantages of incorporating Code Switching and Code Mixing in classroom activities. The research adopted a descriptive qualitative approach and was conducted in the eleventh grade of SMA Plus Al-Amanah, involving two English teachers as participants. Data collection methods encompassed observations, recordings, and interviews. From the gathered data, the identified types of Code Switching included Inter-Sentential Switching, Intra-Sentential Switching, and Tag Switching. In addition, the types of Code Mixing discovered comprised Insertion, Alternation, and Congruent Lexicalization. Notably, the prevalent types utilized in classroom activities were Tag Switching and Insertion. Furthermore, the study uncovered several benefits associated with the utilization of Code Switching and Code Mixing in the classroom. These advantages encompassed enhancing students' comprehension of the subject matter, introducing new vocabulary, and facilitating pronunciation practice. In conclusion, based on the findings, it is recommended that English teachers consider integrating Code Switching and Code Mixing into their teaching and learning processes during classroom activities, as it has been demonstrated to be more effective than exclusively using a single language.